1969
DOI: 10.1002/j.1537-2197.1969.tb07518.x
|View full text |Cite
|
Sign up to set email alerts
|

Leaf Initiation Rates and Volume Growth Rates in the Shoot Apex of Chrysanthemum

Abstract: The leaf initiation rate and apical volume growth rate of lateral shoots of Chrysanthemum morifolium 'Improved Albatross III' were determined for plants growing under controlled environment conditions. After removal of the terminal bud, the top two lateral buds produced leaves at a rate of 1.4 to 1.6 leaves/day for the first 9 or 10 days. At about the 10th day there appeared to be an abrupt shift to a lower initiation rate of 0.7 to 0.8 leaves/day. Defoliation by periodic removal of leaves larger than 1 cm cau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

1970
1970
1988
1988

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 21 publications
0
15
0
Order By: Relevance
“…However, during the early and late phases ofdevelopment, leaf-divergence angles may change significantly. Rates ofleaf initiation remain constant, despite wide variation in environmental factors, and require significant experimental manipulation to change (Berg and Cutter, 1969;Romberger and Gregory, 1977;Green, 1985Green, , 1986; see Hardwick, 1986). Consequently, phyllotactic pattern is frequently a good taxonomic character (Schiiepp, 1959;Rutishauser, 1981Rutishauser, , 1982Rutishauser and Sattler, 1985).…”
Section: Discussionmentioning
confidence: 99%
“…However, during the early and late phases ofdevelopment, leaf-divergence angles may change significantly. Rates ofleaf initiation remain constant, despite wide variation in environmental factors, and require significant experimental manipulation to change (Berg and Cutter, 1969;Romberger and Gregory, 1977;Green, 1985Green, , 1986; see Hardwick, 1986). Consequently, phyllotactic pattern is frequently a good taxonomic character (Schiiepp, 1959;Rutishauser, 1981Rutishauser, , 1982Rutishauser and Sattler, 1985).…”
Section: Discussionmentioning
confidence: 99%
“…Van Iterson (1907) discussed briefly the possibility of constructing contiguous ellipses on various surfaces models but left this project for future investigators. In light of the differences in relative radial and vertical rates of growth observed for Epilobium and other species (Meicenheimer, 1979;Berg and Cutter, 1969) such modeling appears worthwhile. It can be argued that the existing models of phyl-lotaxy which utilize regular lattice cylindrical constructions are transformable into exponentially growing systems, but this transformation combines both radial and vertical growth rates into a single parameter, whereas, in shoot systems that have actually been investigated these rates are different.…”
mentioning
confidence: 99%
“…The shoot apex of maize increases linearly in all of its dimensions, length, width, and thickness, with plastochron stage (Abbe and Phinney, 1951). Berg and Cutter (1969) found that the Chrysanthemum shoot apex increases in size at a constant rate over the nine successive plastochron stages examined.…”
Section: Discussion-mentioning
confidence: 89%